Factors Influencing Human Resource Development of the Tax Department in Luang Prabang Province - CHITTAPHONE, Saychith; Keoboualapheth, Soulideth; Indavong, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The objectives of this research were to study the human resource development conditions of the Tax Department in Luang Prabang Province; to study the importance level of work environment factors of the Tax Department in Luang Prabang Province; and to study the operational environment factors influencing human resource development of the Tax Department in Luang Prabang Province. The population used in the research is the employees of the tax office in Luang Prabang province with a total sample group of 126 people as a specific random sample. The instrument used in the research is a questionnaire with a reliability value equal to 0.947. The statistics used for data analysis were frequency value, mean value, standard deviation value, Pearson’s product-moment coefficient and multiple regression analysis. The results were found that: The conditions of human resource development in Luang Prabang province were mostly about human resources development and the employees were of the opinion that the development of human resources based on the developing of knowledge, skills and attitude of the employees and it is the most necessary thing, the employees have the need to develop foreign languages and upgrade the most specialized subjects. The perceptions of staff towards the practice of human resource development of the Tax Department in Luang Prabang Province was overall at a high level mainly on the practice of implementation human resource development plan, evaluation of implementation, specialized and organization development. It was also viewed that the internal and external factors play a crucial role in the work performance of staff. The employees’ opinions towards the development of human resources of the taxation sector in Luang Prabang province. Overall, there was a very good implementation level of human resources development, such as the implementation of personnel development, performance management, career development and organizational development. Internal environmental factors and external environmental factors in general are very important to the work of employees. The work environment factors that had a positive effect on the development of human resources in terms of personnel development were commitment in the workplace, policy, legal, regulations, and technological progress; the career and organization development are top-level support, work performance results, policy, legal and regulations; The management of the overall performance is the support of the top level, the commitment to work, the performance of the work, the policy and the law. Environmental factors that had a negative effect on the development of human resources in terms of personnel development was the economic growth factor and in terms of overall career development was the information awareness factor.